Comparative Analysis of Gene Expression Patterns for Oral Epithelial Cell Functions in Periodontitis - Gonzalez, Octavio A.; Kirakodu, Sreenatha; Nguyen, Linh M.; Orraca, Luis; Novak, Michael J.; Gonzalez-Martinez, Janis; Ebersole, Jeffrey L. (Frontiers in Oral Health, 2022)
The structure and function of epithelial cells are critical for the construction and maintenance of intact epithelial surfaces throughout the body. Beyond the mechanical barrier functions, epithelial cells have been identified as active participants in providing warning signals to the host immune and inflammatory cells, as well as communicating various detailed information on the noxious challenge to help drive specificity in the characteristics of the host response related to health or pathologic inflammation. Rhesus monkeys were used in these studies to evaluate the gingival transcriptome for naturally occurring disease samples (GeneChip® Rhesus Macaque Genome Array) or for ligature-induced disease (GeneChip® Rhesus Gene 1.0 ST Array) to explore up to 452 annotated genes related to epithelial cell structure and functions. Animals were distributed by age into four groups: ≤3 years (young), 3-7 years (adolescent), 12-16 years (adult) and 18-23 years (aged). For naturally-occurring disease, adult and aged periodontitis animals were used and comprised 34 animals (14 females/20 males). Similar ages with 9 animals per group were included in a ligature-induced periodontitis experiment. A buccal gingival sample from either healthy or periodontitis-affected tissues were collected and microarray analysis performed. The overall results of this investigation suggested a substantial alteration in epithelial cell functions that occurs rapidly with disease initiation. Many of these changes were prolonged throughout disease progression and generally reflect a disruption of normal cellular functions that would presage the resulting tissue destruction and clinical disease measures. Finally, clinical resolution may not signify biological resolution and represent continued risk for disease that may require considerations for additional biologic specific interventions to best manage further disease.